2019
DOI: 10.1177/0020764018820879
|View full text |Cite
|
Sign up to set email alerts
|

Living with schizophrenia: Perspectives of Turkish people with schizophrenia from two Patient Associations on how the illness affects their lives

Abstract: Background: Schizophrenia is a chronic mental illness affecting the social and occupational lives of the sufferers and posing a considerable burden on the patients and their families. Furthermore, negative societal reactions and the internalization of these attitudes exacerbate the difficulties encountered. This study examines the perspectives of Turkish people with schizophrenia on how they view the impact of the illness on their lives, the societal reactions and attitudes to schizophrenia and whether they ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…In support of the above ndings, Karanci et. al, (2019) concluded that medication changed the general wellbeing of persons living with the diagnosis of schizophrenia from bad to good and is generally good for persons with schizophrenia.…”
Section: Discussion Resultssupporting
confidence: 68%
“…In support of the above ndings, Karanci et. al, (2019) concluded that medication changed the general wellbeing of persons living with the diagnosis of schizophrenia from bad to good and is generally good for persons with schizophrenia.…”
Section: Discussion Resultssupporting
confidence: 68%
“…Another reason people stigmatise these individuals may be due to the symptoms people with schizophrenia exhibit, especially in the relapse stage. Such manifestations scare people, especially those in the catchment area where study participants reside [ 41 ]. Hence, most people in the community may consider them highly violent and can even kill people who may get closer to them.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, most people in the community may consider them highly violent and can even kill people who may get closer to them. Society may permanently stigmatise them [ 41 ]. Stigma affects the well-being of people with schizophrenia because it leads to isolation and rejection of these victims.…”
Section: Discussionmentioning
confidence: 99%
“…People's perception of schizophrenia and how they label people with the condition make it very challenging for individuals living with the need to cope with it, especially when they step out of their homes [37]. They, therefore, respond to these unfortunate situations by using defense mechanisms such as avoidance, denial and resorting to wishful thinking [38][39][40][41]. They sometimes have no other choice of facing stigma rather than resorting to these strategies in maintaining their well-being.…”
Section: Discussionmentioning
confidence: 99%